Analisis Promosi terhadap Minat Beli Konsumen dengan Harga sebagai Variabel Intervening Produk Pospay (Studi Kasus PT. Pos Indonesia Cabang Binjai Provinsi Sumatera Utara) - Rahmi, Aulia; Manuntun Pakpahan; Dian Septiana Sari (Universitas Muhammadiyah Surabaya, 2024)
The research analysis aims to find out whether promotions influence purchasing interest through price as an intervening variable in Pt's Pospay service products. Pos Indonesia Binjai branch. The data analysis technique used is the associative method with the help of the SPSS version 25.0 program. This research uses multiple linear regression analysis. The sample in this study was 96 respondents. Primary data collection uses a questionnaire. The results of the research show that promotions partially have a positive and significant effect on the prices of Pt's Pospay service products. Pos Indonesia Binjai branch. Promotion partially has a positive and significant effect on purchasing interest in Pt's Pospay service products. Pos Indonesia Binjai branch. Price partially has a positive and significant effect on purchasing interest in Pt's Pospay service products. Pos Indonesia Binjai branch. Promotion and price simultaneously have a positive and significant effect on purchasing interest in Pt's Pospay service products. Pos Indonesia Binjai branch. Promotions influence purchasing interest through price as an intervening variable in Pt's Pospay service products. Pos Indonesia Binjai branch.